2003
DOI: 10.2134/agronj2003.9940
|View full text |Cite
|
Sign up to set email alerts
|

Yield Goal versus Delta Yield for Predicting Fertilizer Nitrogen Need in Corn

Abstract: Fertilizer N needs of corn (Zea mays L.) vary widely both among and within fields. Many states use yield goal to help determine differences in fertilizer N need, but some states have questioned yield goal–derived recommendations because of the poor correlation of yield with fertilizer N need. In this study, data from 298 previously reported experiments in five states (Illinois, Minnesota, Missouri, Pennsylvania, and Wisconsin) were combined to evaluate fertilizer N response of corn. Corn grain yield at the eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 20 publications
5
91
0
2
Order By: Relevance
“…Precision Agric (2010) 11:291-305 301 Interest in predicting delta yield during vegetative growth stages stems from previous work by Lory and Scharf (2003) who showed that EONR was related to delta yield (R 2 = 0.65) from 32 sites in Missouri. Combining the relationships identified in that research with the findings here, color differences between fertilized and unfertilized corn could be used to predict delta yield and a site-specific EONR estimated for side-dressed applications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Precision Agric (2010) 11:291-305 301 Interest in predicting delta yield during vegetative growth stages stems from previous work by Lory and Scharf (2003) who showed that EONR was related to delta yield (R 2 = 0.65) from 32 sites in Missouri. Combining the relationships identified in that research with the findings here, color differences between fertilized and unfertilized corn could be used to predict delta yield and a site-specific EONR estimated for side-dressed applications.…”
Section: Resultsmentioning
confidence: 99%
“…1). Previous work showed delta yield to be more related to EONR than to realistic expectations of yield (Lory and Scharf 2003). The EONR and delta yield were related to the four relative color indices described above using SAS PROC REG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of applied N depends on weather factors influencing soil temperature and moisture (Westerman et al 2000), soil N status, water availability, hybrid ability to take up N (Ma and Dwyer 1998;Ma et al 1999a), and plant population density of maize (Al-Kaisi and Yin 2003). Soil N supply is expected to vary among years and locations (Lory and Scharf 2003). In a humid environment such as eastern Ontario, maize yield response to N amendments is poorly correlated with soil mineral N content before planting because of great spatial and temporal variability (Katsvairo et al 2003;Ma and Dwyer 1999;.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, losses as nitrous oxide (N 2 O) due to denitrification contribute to global warming, while losses as ammonia (NH 3 ) due to volatilization contribute to soil acidification when it returns to the land. Accurate fertilizer N recommendations can reduce N loss (Lory and Scharf 2003).…”
Section: Introductionmentioning
confidence: 99%